Analisis Efektivitas Pemeriksaan Akuntansi Terhadap Pengendalian Internal Akuntansi - Ayu Ceria Dewi Lubis; Reza Hanafi Lubis (Program Studi Akuntansi Fakultas Ekonomi UMN AL Washliyah, 2025)
In the context of increasingly complex accounting industry developments, the need for better services is very urgent. This is due to several factors that affect public trust in financial reports and auditor performance. Accounting audit is a crucial process in ensuring the accuracy and reliability of a company's financial information. Accounting audit is not only determined by the skills and expertise of the auditor, but also influenced by the quality of internal control implemented by the company. Internal control functions to minimize losses that may be caused by the company's operations. This allows for quick action to improve the quality of the company in accordance with the targets that have been set. General control aims to ensure stability and a well-managed control environment in an organization, which helps in the implementation of effective application controls. This study uses Descriptive qualitative research is a research approach that aims to describe a particular phenomenon, event, or problem. Descriptive qualitative research methods conducted only through literature studies offer an in-depth understanding of the topic being studied without the need to collect primary data. The results of this study indicate that internal control plays an important role in supporting the effectiveness of accounting audits and achieving overall company goals. Good internal control can help companies manage risk, improve financial performance, protect assets, improve information quality, ensure regulatory compliance, and improve operational efficiency. Therefore, company management needs to pay attention to and continuously improve their internal control system to achieve long-term success in a dynamic and complex business environment. Keywords: Internal Control, Accounting Audit